Nanofibrillated cellulose (CNF) from eucalyptus sawdust as a dry strength agent of unrefined eucalyptus handsheets - Vallejos, María Evangelina (2016)
Nanofibrillated cellulose has been obtained from the cellulosic fraction of eucalyptus sawdust. The fractionation process involved the partial removal of hemicelluloses and lignin. CNF was obtained using TEMPO oxidation with NaOCl in basic medium followed by mechanical homogenization. The obtained CNF was subsequently used as a dry strength agent on unbleached unrefined eucalyptus pulp. The addition of 3, 6 and 9 wt.% of CNF increased lineally the tensile index of handsheets to about 55 N m g−1 at 35°SR, compatible with papermachine runnability. The other mechanical properties also increased substantially, and porosity decreased moderately. The estimated specific surface and average diameter of these CNF were 60 m2 g−1, and of 41.0 nm, respectively. The addition of 9 wt.% of CNF produced an increase in mechanical strength, equivalent to that produced by PFI refining at 1600 revolutions